Business Process Engineering of Opening a Simpedes Saving Account Using Value-Added and Flow Analysis Methods - Vinny Putri Rezeki; Fitria Fitria (Kresnamedia Publisher, 2023)
The level of competition and demands for higher business quality encourage the company to develop in all sectors to achieve company goals, including the banking sector, which has main business processes, one of which is serving customers in the account opening process. Therefore, this study conducted a business process analysis to open a Simpedes savings account and then build a more optimal business process improvement engineering. Business process engineering by conducting business process analysis using the BPMN standard, value-added analysis, flow analysis, and simulation using the Bizagi Modeler software. Based on the simulation at Level 2-Time Analysis, the existing business process takes 52 minutes to complete 22 activities. Meanwhile, business process improvement only takes 19 minutes for 16 account opening activities. According to the accumulated calculations, the simulation results on the Level 3-Resource Analysis business process improvement with the implementation of writing pad procurement and the raw material utilization will increase by 13,23%. The costs incurred at the beginning will be significant but have long-term benefits so that the results of business process engineering show better improvements in terms of time and cost that companies can use as business process optimization recommendations.